2018
DOI: 10.1016/j.sbi.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Directed evolution to improve protein folding in vivo

Abstract: Recently, several innovative approaches have been developed that allow one to directly screen or select for improved protein folding in the cellular context. These methods have the potential of not just leading to a better understanding of the in vivo folding process, they may also allow for improved production of proteins of biotechnological interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…Likewise, the abundant presence of misfolded polypeptides with weak folding mutations disrupts the balance of the protein-folding quality control and can establish aberrant physical and genetic interactions that interfere with the folding of marginally stable proteins (Gidalevitz et al 2006(Gidalevitz et al , 2009. Remarkably, directed evolution experiments have shown that more stable proteins can readily be engineered from marginally stable proteins (Foit et al 2009;Sachsenhauser and Bardwell 2018). This shows that most cellular proteins have not been optimized for maximum but optimum stability and suggests that the stability of the proteome is subject to functional constraints.…”
Section: Protein-intrinsic Factors That Regulate Protein Solubility Amentioning
confidence: 99%
“…Likewise, the abundant presence of misfolded polypeptides with weak folding mutations disrupts the balance of the protein-folding quality control and can establish aberrant physical and genetic interactions that interfere with the folding of marginally stable proteins (Gidalevitz et al 2006(Gidalevitz et al , 2009. Remarkably, directed evolution experiments have shown that more stable proteins can readily be engineered from marginally stable proteins (Foit et al 2009;Sachsenhauser and Bardwell 2018). This shows that most cellular proteins have not been optimized for maximum but optimum stability and suggests that the stability of the proteome is subject to functional constraints.…”
Section: Protein-intrinsic Factors That Regulate Protein Solubility Amentioning
confidence: 99%
“…Examples include fusion reporter proteins for assessing protein folding and solubility using fluorescence, enzymatic reactions, antibiotic resistance or ligand binding as reporters for the production of soluble and folded proteins. [16][17][18][19][20] and their promotors may be used to drive stress induced heterologous protein expression 21 . Thus, chaperone promoters can be used to construct reporters for the presence of e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme engineering, for improved catalytic efficiency, substrate and product preferences, and solubility, is traditionally used as a strategy to overcome issues with product synthesis. It can, however, be time‐consuming, even when aided by computational protein engineering tools (e.g., Hassanpour, Ullah, Yousofshahi, Nair, & Hassoun, ; Sachsenhauser & Bardwell, ), especially if several enzymes within a pathway are insoluble. Thus, implementing pathways with the knowledge that the enzymes selected have a high propensity for solubility in the host can reduce the traditional trial‐and‐error approach to enzyme selection.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme engineering, for improved catalytic efficiency, substrate and product preferences, and solubility, is traditionally used as a strategy to overcome issues with product synthesis. It can, however, be time-consuming, even when aided by computational protein engineering tools (e.g., Hassanpour, Ullah, Yousofshahi, Nair, & Hassoun, 2017;Sachsenhauser & Bardwell, 2018), F I G U R E 6 Three pathways for producing 3-hydroxypropanoic acid (3-HP) in E. coli were identified by ProPASS and proposed by (a) Luo et al (2016), (b) Cheng et al (2016), and (c) Song et al (2016). Two predicted solubility scores are provided for each enzymatic reaction.…”
Section: 3-butanediolmentioning
confidence: 99%